2013
DOI: 10.1179/1743294413y.0000000113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC concentration in electrolyte on Ni–SiC composite coating properties

Abstract: In the present study, a nickel sulphate bath containing SiC particles between 0?5 and 5?0 mm has been used as the plating electrolyte to obtain Ni-SiC composites on copper surfaces with high hardness and wear resistance for using in antiwear applications such as dies, tools and working parts of automobiles. The influence of SiC concentration in the electrolyte on morphology, microhardness, friction coefficient and wear missing volume of coatings has been studied. The coatings were analysed with scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…Nanoparticles are always used to be incorporated in metal and metal alloy coatings to enhance their mechanical and chemical properties [3][4][5][6][7][8]. Aghaie et al [4] electrodeposited Ni-SiC composites on copper surface and found that increasing the concentration of SiC particles in the Watts bath results in the improvement of coating microhardness and the decrease of the friction coefficient and wear missing volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles are always used to be incorporated in metal and metal alloy coatings to enhance their mechanical and chemical properties [3][4][5][6][7][8]. Aghaie et al [4] electrodeposited Ni-SiC composites on copper surface and found that increasing the concentration of SiC particles in the Watts bath results in the improvement of coating microhardness and the decrease of the friction coefficient and wear missing volume.…”
Section: Introductionmentioning
confidence: 99%
“…Aghaie et al [4] electrodeposited Ni-SiC composites on copper surface and found that increasing the concentration of SiC particles in the Watts bath results in the improvement of coating microhardness and the decrease of the friction coefficient and wear missing volume. Kasturibai et al [5] found that the microhardness and corrosion resistance of Ni-Si 3 N 4 nanocomposite coating were higher and better than those of the pure Ni coating.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, the microhardness, corrosion, and wear-resistant properties of electrodeposited Ni coatings have been increased by incorporating abrasive particles like alumina, diamond, SiC, ZrC, ZrO 2 , etc. [1][2][3][4][5][6][7][8][9]. However, the COF of such coatings has always been higher.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…This phenomenon demonstrates that the weight percent of the CeO 2 nanoparticles embedded into the composite electrodeposits is significantly affected by current density. Many researchers also stated that the embedded nanoparticle content reduced with a rise in the current density [13][14][15].…”
Section: Please Scroll Down For Articlementioning
confidence: 99%